China - 40-Year Experience in Renewable Energy Development : Policies, Achievements, and Lessons Learned - World Bank (World Bank, Washington, DC, 2021)
China made impressive progress in developing renewable energy to provide access to clean energy and electricity to its predominantly rural population before the economic boom that followed the open door policy, by improving energy supply to the economy as the country industrialized and urbanized at an extremely fast pace and finally by fighting debilitating local pollution and mitigating the impact of climate change. Through that journey, China has accumulated a considerable amount of experience and learned many lessons. Its evolution from a low-income to a middle-high income country and its wide geographical diversity brought about extensive challenges, many of which are similar to those facing a wide range of developing countries who are willing to further rely on renewable energy to address their energy needs. This report attempts to present the Chinese rich and diversified experience and draw the lessons learned that may inform decision-making in these countries.